Multiple Victimizations and Overdose Among Women With a History of Illicit Drug Use. Issue 3 (February 2022) - Ataiants, Janna; Mazzella, Silvana; Roth, Alexis M.; Robinson, Lucy F.; Sell, Randall L.; Lankenau, Stephen E.
The experiences of violence and overdose are highly prevalent among women who use illicit drugs. This study sought to ascertain whether multiple victimizations during adulthood increase the frequency of women's overdose. The sample comprised 218 women recruited at Philadelphia harm reduction sites during 2016–2017. Victimization was assessed as exposure to 16 types of adulthood violence. Three measures were constructed for multiple victimizations: continuous and categorical polyvictimization, and predominant violence domain. Negative binomial regression estimated the incidence rate ratio (IRR) of lifetime overdoses from multiple victimizations. Lifetime history of opioid use (88.6%) and drug injection (79.5%) were common. Among overdose survivors (68.5%), the median of lifetime overdoses was 3. The majority of participants (58.7%) were victims of predominantly sexual violence, 26.1% experienced predominantly physical abuse/assault, and 3.7% were victims of predominantly verbal aggression/coercive control. Participants reported a mean of seven violence types; the higher-score category of polyvictimization (9–16 violence types) comprised 41.7% of the total sample. In multivariable models, one-unit increase in continuous polyvictimization was associated with 4% higher overdose rates (IRR: 1.04, 95% confidence interval [CI]: [1.00, 1.08]). Compared to women who were not victimized (11.5%), those in the higher-score category of polyvictimization (IRR: 2.01; 95% CI: [1.06, 3.80]) and exposed to predominantly sexual violence (IRR: 2.10, 95% CI: [1.13, 3.91]) were expected to have higher overdose rates. Polyvictimization and sexual violence amplified the risk of repeated overdose among drug-involved women. Female overdose survivors need to be screened for exposure to multiple forms of violence, especially sexual violence. Findings underscore the need to scale-up victimization support and overdose prevention services for disenfranchised women.